Challenges and opportunities in point-of-care ultrasound: A qualitative exploration of respiratory physiotherapists' experiences of lung ultrasound training and its adoption in critical care. (May 2022) - Hayward, Simon; Innes, Sue; Smith, Mike
Introduction: Diagnostic lung ultrasound (LUS) is gaining popularity among respiratory physiotherapists as an imaging modality to aid pulmonary assessments, guide intervention selection, and monitor the efficacy of chosen interventions. The ability of respiratory physiotherapists to incorporate LUS into their clinical practice is influenced by multiple factors to adoption and implementation. The aim of this study was to explore the experiences of senior respiratory physiotherapists who have attempted to adopt and implement LUS into their clinical practice in critical care. It is hoped these experiences will inform the development of educational and adoption strategies for the future implementation of LUS. Methods: Following a national call out, eight senior critical care respiratory physiotherapists were purposively selected to be interviewed using semi-structured questions exploring their varied experiences of LUS adoption into clinical practice in critical care. The transcribed data were thematically analysed. Results: Five main themes emerged from the participants' responses: (i) support for physiotherapists using LUS, (ii) knowledge and understanding of LUS evidence, (iii) governance, (iv) physiotherapists' motivation to use LUS, and (v) resources. Quotes for each of the five themes are given as exemplars. Conclusion: Participants reported a range of factors that influenced their ability to adopt and implement LUS into practice several were enabling, and others were barriers to progress. Online Appendix 1 contains recommendations from the authors to help guide managers and clinicians wishing to adopt LUS into respiratory physiotherapy services and patient pathways.